Genome-wide transcript analysis of early maize leaf development reveals gene cohorts associated with the differentiation of C4 Kranz anatomy - Wang, P; Kelly, S; Fouracre, J; Langdale, J (2013)
Photosynthesis underpins the viability of most ecosystems, with C 4 plants that exhibit 'Kranz' anatomy being the most efficient primary producers. Kranz anatomy is characterized by closely spaced veins that are encircled by two morphologically distinct photosynthetic cell types. Although Kranz anatomy evolved multiple times, the underlying genetic mechanisms remain largely elusive, with only the maize scarecrow gene so far implicated in Kranz patterning. To provide a broader insight into the regulation of Kranz differentiation, we performed a genome-wide comparative analysis of developmental trajectories in Kranz (foliar leaf blade) and non-Kranz (husk leaf sheath) leaves of the C4 plant maize. Using profile classification of gene expression in early leaf primordia, we identified cohorts of genes associated with procambium initiation and vascular patterning. In addition, we used supervised classification criteria inferred from anatomical and developmental analyses of five developmental stages to identify candidate regulators of cell-type specification. Our analysis supports the suggestion that Kranz anatomy is patterned, at least in part, by a SCARECROW/SHORTROOT regulatory network, and suggests likely components of that network. Furthermore, the data imply a role for additional pathways in the development of Kranz leaves. © 2013 John Wiley and Sons Ltd.